2023
DOI: 10.1007/s11218-023-09777-z
|View full text |Cite
|
Sign up to set email alerts
|

Addressing racial misinformation at school: a psycho-social intervention aimed at reducing ethnic moral disengagement in adolescents

Abstract: The present study aims to examine whether by promoting the socio-analytic thinking it is possible to intervene in the reliance on ethnic moral disengagement as a negative consequence of racial misleading news, that can seriously contribute to the diffusion of ethnic prejudice. We focus on the neglected phenomenon of racial hoaxes, which can be defined as misleading news stories dealing with health or safety threats, in which the protagonist is described in terms of ethnicity or nationality. The intervention pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…In terms of practical implications, technologies can support self-efficacy beliefs, which are malleable and influence self-determined behavioral change through direct or mediated experience (as in this case); indeed, technology has been shown to have the potential to enhance regulation and critical thinking skills ( Kitsantas et al, 2019 ). In the case of adolescents, social networks are the new social laboratory within which they can learn behavioral regulation strategies (modeling) even from “positive” peers who provide alternative models of coping with online misinformation, but they can also have mediated experiences through games or targeted applications ( D’Errico et al, 2023 ) that challenge and develop their ability to regulate themselves before sharing unreliable news.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of practical implications, technologies can support self-efficacy beliefs, which are malleable and influence self-determined behavioral change through direct or mediated experience (as in this case); indeed, technology has been shown to have the potential to enhance regulation and critical thinking skills ( Kitsantas et al, 2019 ). In the case of adolescents, social networks are the new social laboratory within which they can learn behavioral regulation strategies (modeling) even from “positive” peers who provide alternative models of coping with online misinformation, but they can also have mediated experiences through games or targeted applications ( D’Errico et al, 2023 ) that challenge and develop their ability to regulate themselves before sharing unreliable news.…”
Section: Discussionmentioning
confidence: 99%
“…By promoting socio-analytical thinking via providing an alternate perspective of an immigrant, the intervention was shown to reduce racial biases when dealing with racially motivated misinformation. As mis-and disinformation online often relies on racial biases and prejudices (Papapicco et al, 2022;D'Errico et al, 2023), interventions such as this could provide vital methods for countering the functional mechanisms (e.g., racial prejudice) that help false information spread online.…”
Section: Discussionmentioning
confidence: 99%
“…Positive contact conditions involve envisioning the out-group person in close physical proximity, while in control conditions the out-group person is utterly absent (Bagci et al, 2018). The threat hypothesis suggests that threatening out-group members are represented as physically close to the alert observer (Fini et al, 2018). Physical proximity between members of competing groups is associated with the risk of losing status, increased hostility, and a desire to maintain distance to restore safety boundaries (Xiao et al, 2016).…”
Section: Physical Closenessmentioning
confidence: 99%
“…A meta-analysis has provided strong evidence for the effectiveness of positive imagined contact ( Miles and Crisp, 2014 ). Studies have shown the effectiveness of imagined contact and related non-direct contact in improving intergroup attitudes and relations among individuals spanning from childhood through adulthood ( Turner and Crisp, 2010 ; Zhou et al, 2019 ; Nasie et al, 2022 ; D’Errico et al, 2023 ). These studies, among others, have revealed improvements across a wide range of outcome variables, including out-group trust ( Turner et al, 2013 ), contact self-efficacy ( Stathi et al, 2011 ), humanization ( Prati and Loughnan, 2018 ), positive behaviours toward out-group members ( Turner and West, 2012 ), and ethnic moral disengagement ( D’Errico et al, 2023 ).…”
Section: How Can Imagined Contact Promote Positive Interactions With ...mentioning
confidence: 99%
See 1 more Smart Citation